2019
DOI: 10.1029/2019gl084450
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Film Thickening in Porous Media

Abstract: Methane hydrate formation accompanied by upward migration of methane in sediments was studied. Methane hydrate film forms initially along the interface between the gas and surrounding pore fluid when methane reaches the hydrate stability zone. Subsequent film thickening and related mass transfer are critical but have not been studied previously. Experimental and theoretical studies were performed to investigate the film thickening and rate-limiting mechanisms. Initial gas density affects the stability of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This study focuses on the influence of hydrate on the geomechanical behavior of hydrate‐bearing sediments. Detailed descriptions on the hydrate formation process and resultant hydrate morphology in pore spaces are covered in previous works (Lei & Seol, ; Lei, Seol, Choi, & Kneafsey, ; Lei, Seol, & Myshakin, ). CT scan configuration and CT image processing are in Lei et al ().…”
Section: Methodsmentioning
confidence: 99%
“…This study focuses on the influence of hydrate on the geomechanical behavior of hydrate‐bearing sediments. Detailed descriptions on the hydrate formation process and resultant hydrate morphology in pore spaces are covered in previous works (Lei & Seol, ; Lei, Seol, Choi, & Kneafsey, ; Lei, Seol, & Myshakin, ). CT scan configuration and CT image processing are in Lei et al ().…”
Section: Methodsmentioning
confidence: 99%
“…In practice, gas hydrate growth rates even in passive systems tend to be faster than would be anticipated by assuming growth occurs only via diffusion of methane or water through the full thickness of the gas hydrate film. Several studies have shown that the gas hydrate interfaces tend to crack as they form (Jin et al, 2012; Lei et al, 2019; Tohidi, Østergaard, et al, 2001; Warzinski et al, 2014), creating pathways for more rapidly combining methane and water to form additional gas hydrate.…”
Section: Rates Of Hydrate Phase Transitionsmentioning
confidence: 99%
“…Even though hydrate is solid, it can move through dissolution and reformation (e.g., Liu & Flemings, 2011). Regardless of how hydrate nucleates in a system, hydrate growth behaves similarly to a mobile, nonwetting phase that will rearrange itself to minimize energy through Ostwald ripening type behavior (e.g., Chen & Espinoza, 2018; Lei, Seol, & Myshakin, 2019). This movement is driven by minimizing free energy, and the hydrate/water interface minimizes its energy by deforming to a state of constant curvature.…”
Section: Relative Permeabilitymentioning
confidence: 99%